Post-treatment lymphocytopaenia, integral body dose and overall survival in lung cancer patients treated with radical radiotherapy. (June 2019) - Joseph, Nuradh; McWilliam, Alan; Kennedy, Jason; Haslett, Kate; Mahil, Jasmin; Gavarraju, Abhilash; Mistry, Hitesh; Van Herk, Marcel; Faivre-Finn, Corinne; Choudhury, Ananya
Highlights: Post-treatment lymphocytopaenia is a complication of thoracic radiotherapy. A high integral body dose is associated with lower post-treatment lymphocyte counts (LC) Post-treatment lymphocytopaenia is associated with poor overall survival. It is a potential biomarker for selection of patients suitable for immune modulation. Abstract: Introduction: Post-treatment lymphocytopaenia is a recognized complication of thoracic radiotherapy likely due to irradiation of a large volume of circulatory blood. We hypothesize that post-treatment absolute lymphocyte count (ALC) is associated with integral body dose and overall survival (OS) in lung cancer patients treated with radical radiotherapy. Materials and methods: Data on clinicopathological variables, dosimetric parameters, and pre and post-treatment blood counts were collected retrospectively in 217 lung cancer patients (131 with non-small cell lung cancer and 86 with small cell lung cancer) treated with radical radiotherapy. Induction chemotherapy followed by radiotherapy and concurrent chemoradiotherapy were delivered in 89 (42%) and 99 (47%) patients respectively. Multiple stepwise regression analysis was performed separately for ALC and absolute neutrophil count (ANC) to derive a model for prediction of post-treatment count and multivariate analysis was performed for OS using a Cox regression model. Results: There was a significant decline in post-treatment counts for both ANC and ALC ( p  < 0.001). Multiple stepwise linear regression analysis confirmed pre-treatment ALC, body integral dose and use of concurrent chemotherapy as significant predictors of post-treatment ALC ( R 2  = 0.33, F (4, 212) = 26.6 p  < 0.001). Pre-treatment ANC, integral heart dose and number of fractions were significant predictors of post-treatment ANC ( R 2  = 0.18, F (3, 213) = 16.38 p  < 0.001). Low post-treatment ALC, high pre-treatment ANC, high planning target volume integral dose and lower number of fractions were predictive of inferior OS. Conclusions: There is a negative correlation between integral body dose and post-treatment ALC which is an adverse prognostic factor in lung cancer patients treated with radical radiotherapy.